O uso do brise-soleil na arquitetura da região central do Rio Grande do Sul - Weber, Caroline Pienes (2005)
The brise-soleil appeared due to the protection need against excessive solar radiation, which can cause discomfort for the high heat and the disarray in the admission of natural light. Apart from this function, that element has got a significative formal expression, contributing in the formal composition of the architecture. This work was developed in the Central Region of the Rio Grande do Sul State, aiming at questioning the use of this type of external solar protector by architects and engineers, evaluating the readiness of the brise product for commercialisation, as well as presenting and analysing different typologies of brise-soleil employed in the region's architecture. The research has as hypothesis that the knowledge regarding the brise-soleil would contribute to its correct use, as much as an element of protection against the incidence of solar rays, as an architectural element in the formal composition of architecture. From this research, it was observed the real reasons for the lack of use of that device on the planner's part, besides presenting the limitations and potentialities of the industrialised brise and to show through examples from the local architecture the relevant aspects which contribute to the appropriate insert of this important environmental and architectural element.